2018
DOI: 10.1038/s41598-018-34216-x
|View full text |Cite
|
Sign up to set email alerts
|

Pathological cardiac remodeling occurs early in CKD mice from unilateral urinary obstruction, and is attenuated by Enalapril

Abstract: Cardiovascular disease constitutes the leading cause of mortality in patients with chronic kidney disease (CKD) and end-stage renal disease. Despite increasing recognition of a close interplay between kidney dysfunction and cardiovascular disease, termed cardiorenal syndrome (CRS), the underlying mechanisms of CRS remain poorly understood. Here we report the development of pathological cardiac hypertrophy and fibrosis in early stage non-uremic CKD. Moderate kidney failure was induced three weeks after unilater… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 93 publications
(76 reference statements)
2
34
0
Order By: Relevance
“…In addition, unilateral ureteral obstruction (UUO) can induce some cardiac hypertrophy and fibrosis [79,92]. However, since UUO does not cause renal failure in the presence of a non-injured contralateral kidney, the model is probably not suitable to induce a severe cardiac phenotype.…”
Section: Surgically Induced Modelsmentioning
confidence: 99%
“…In addition, unilateral ureteral obstruction (UUO) can induce some cardiac hypertrophy and fibrosis [79,92]. However, since UUO does not cause renal failure in the presence of a non-injured contralateral kidney, the model is probably not suitable to induce a severe cardiac phenotype.…”
Section: Surgically Induced Modelsmentioning
confidence: 99%
“…In the present study, while no strong changes in renal AT1R expression were observed in enalapril-treated mice, part of the reduction in renal inflammation and damage can also be due to the expected reduction of AngII peptide, since enalapril is a strong ACE inhibitor. AngII has been associated to kidney inflammation in several models (Theuer et al, 2002;Altunoluk et al, 2006;Benigni et al, 2011;Nagasawa et al, 2012;Kanda et al, 2016;Ham et al, 2018;Panico et al, 2019), and the FIGURE 7 | Carboxypeptidase M mRNA expression in renal tissue and mouse epithelial tubular cells. The panels show CPM mRNA expression (A) in mice 24 h after treatment with cisplatin or cisplatin plus enalapril and CPM mRNA expression (B) in mouse tubular cells after treatment with cisplatin or enalaprilat plus cisplatin.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have revealed that ACE influences the regulation of both kinin receptors in vascular smooth muscle cells (Ignjacev-Lazich et al, 2005). Moreover, it has already been shown that ACE inhibition protects against some types of renal disease (Ghosh et al, 2009(Ghosh et al, , 2012Vejakama et al, 2012;Ding et al, 2014;Ham et al, 2018;Panico et al, 2019), including cisplatin-induced kidney disfunction (El-Sayed el et al, 2008), but only renal function and reactive oxygen species were assessed in this work. Given that (a) inflammation has an important role in cisplatin nephrotoxicity; (b) AngII influences the regulation of inflammation-related genes; and (c) ACE inhibition reduces kinin degradation, we decided to verify whether the protective effect of ACE inhibition on the attenuation of cisplatin nephrotoxicity is related to KKS regulation.…”
Section: Introductionmentioning
confidence: 90%
“…Prolyl hydroxylase (PHD) inhibitors, stabilizers of hypoxia-inducible factors (HIFs), have been used to treat acute organ injuries such as renal ischemia-reperfusion, myocardial infarction, and, in some contexts, chronic kidney disease [ 93 ]. Enarodustat (PHD inhibitor) proved to reduce cardiac hypertrophy and fibrosis in a unilateral urinary obstruction (UUO) model in mice [ 94 ]. Moreover, enarodustat counteracted kidney fibrosis reducing pro-inflammatory cytokine expression, apoptosis, and improving capillary density in a nephrectomy model [ 93 ].…”
Section: Oxidative Stress and Endothelial Dysfunction And Cvdmentioning
confidence: 99%